2018
DOI: 10.1089/jmf.2017.0016
|View full text |Cite
|
Sign up to set email alerts
|

Annurca Apple Nutraceutical Formulation Enhances Keratin Expression in a Human Model of Skin and Promotes Hair Growth and Tropism in a Randomized Clinical Trial

Abstract: Several pharmaceutical products have been formulated over the past decades for the treatment of male and female alopecia, and pattern baldness, but relatively few metadata on their efficacy have been published. For these reasons, the pharmaceutical and medical attention has recently focused on the discovery of new and safer remedies. Particularly, great interest has been attracted by oligomeric procyanidin bioactivity, able to promote hair epithelial cell growth as well as to induce the anagen phase. Specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 57 publications
0
48
0
5
Order By: Relevance
“…In this context, recent preclinical evidence and clinical trials have shown an Annurca apple extract (AMS) as a nutraceutical able to effectively counteract adult baldness and patterned hair loss caused by various factors, including androgenetic and metabolic ones. Indeed, significant results in terms of increased hair growth, hair number, hair weight, and keratin content could be measured after two months of oral treatment [24]. The active ingredient behind this formulation is a dry extract derived from the Annurca apple, a variety particularly rich in oligomeric procyanidins, among natural polyphenols belonging to the broader class of bioflavonoids [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, recent preclinical evidence and clinical trials have shown an Annurca apple extract (AMS) as a nutraceutical able to effectively counteract adult baldness and patterned hair loss caused by various factors, including androgenetic and metabolic ones. Indeed, significant results in terms of increased hair growth, hair number, hair weight, and keratin content could be measured after two months of oral treatment [24]. The active ingredient behind this formulation is a dry extract derived from the Annurca apple, a variety particularly rich in oligomeric procyanidins, among natural polyphenols belonging to the broader class of bioflavonoids [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Annurca apples have been repeatedly extracted with water, and the obtained solution was filtered, centrifuged, and concentrated. Then, the solution was spry-dried in combination with maltodextrins, obtaining a fine powder named AnnurMetS (AMS) [24], actually branded as AnnurtriComplex ® . The supplement was formulated by the Department of Pharmacy, University of Naples "Federico II" (Naples, Italy), while large-scale production was accomplished by MB-Med Company (Turin, Italy).…”
Section: Preparation Of Annurca-based Nutraceutical Formulation (Annumentioning
confidence: 99%
See 2 more Smart Citations
“…The supplement can be prepared with the addition of biotin, zinc, and selenomethionine (AMSbzs) or without (AMS). Both supplements lead to improvement in all hair clinical parameters, with the AMSbzs cohort demonstrating increased hair density by 125.2%, hair weight by 42.1%, and keratin content by 40.1% at 2 months [60]. Procyanidins also upregulate MAPK/extracellular signal-related kinase kinase (MEK) in hair epithelial cells and counteract hair growth inhibitory effects of TGF-β in vitro, which may account for these clinical results [61,62].…”
Section: Procyanidinmentioning
confidence: 97%